Avaliação da microdensidade vascular como fator prognóstico em sarcomas de tecidos moles em pequenos animais - Silveira, Matheus Folgearini (2009)
Soft tissue sarcomas are mesenchymal origin neoplasms collectively classified according to histological characteristics and biological behaviour similiarities. Various neoplasms are included in this major group, as fibrosarcoma, hemangiosarcoma, peripheral nerve sheath tumor, myxosarcoma, liposarcoma, leiomyosarcoma, rhabdomiosarcoma, malignant fibrous histiocytoma, synovial cell sarcoma and undifferentiated sarcoma. The microvessel density measure has been applied to investigate tumor angiogenesis in many neoplasms. The objectives of this study were to evaluate de microvessel density in canine and feline soft tissue sarcomas and compare the general vessel measurement area and intense vascular areas hot spot. Those data were compared to usually applied prognostic factors like mitotic index, necroses presence and amount and cellular differentiation. Soft tissue sarcomas were collected in Laboratório Regional de Diagnóstico da Universidade Federal de Pelotas from 1978 to 2008 among canine and feline necropsies and biopsies. In a total of 1668 neoplasms cases during this period, 100 were soft tissue sarcomas, 87 canine and 13 feline. Sex prevalence was not observed in the analyzed species. The major prevalence in canine were hemangiosarcomas (n=34) and fibrosarcomas (n=20), being the mongrel dogs (n=35) most. The large breeds presented major frequence (n=22), followed by medium size (n=16) and small sized breeds (n=9). . In feline population, there were not accentuated prevalence, exciding hemangiosarcomas (n=4) and fibrosarcomas (n=4). In those 100 cases, 39 paraffin blocks were obtained, being 36 canine and 3 feline, mostly mongrel specimens, with 9,21(±2,99) medium age. The general vascular and hot spot areas were significantly correlated (r2=0,98; p<0,01). The mitotic index between areas were in those areas (r2=0,95, p<0,01). Hemangiosarcomas presented major vascular media in the techniques, followed by muscular sarcomas and fibrosarcomas (p<0,05). The microvessel density in soft tissue sarcomas do not present correlation to other prognostic factor usually applied. Hot spot areas can be utilized to determine the vascular degree and mitotic index in soft tissue sarcomas.